1996
DOI: 10.1128/jb.178.20.6064-6066.1996
|View full text |Cite
|
Sign up to set email alerts
|

A two-component response regulator, gltR, is required for glucose transport activity in Pseudomonas aeruginosa PAO1

Abstract: A 729-bp open reading frame (gltR) was identified in Pseudomonas aeruginosa PAO1 that encodes a product homologous to the two-component response regulator family of proteins. Disruption of gltR caused loss of glucose transport activity. Restoration of gltR resulted in wild-type levels of glucose transport. These findings indicate that gltR is required for expression of the glucose transport system in P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…In Pseudomonas aeruginosa, Sage et al (32) reported that the gltR gene encoded a product homologous to the response element of two-component systems, whose disruption caused the loss of glucose transport activity. Inactivation of the gltR-2 gene in P. putida had an effect on growth in the presence of glucose that resulted in a prolonged lag when cells were transferred, for example, from M9 minimal medium with citrate to glucose-containing medium as the sole C source.…”
Section: Discussionmentioning
confidence: 99%
“…In Pseudomonas aeruginosa, Sage et al (32) reported that the gltR gene encoded a product homologous to the response element of two-component systems, whose disruption caused the loss of glucose transport activity. Inactivation of the gltR-2 gene in P. putida had an effect on growth in the presence of glucose that resulted in a prolonged lag when cells were transferred, for example, from M9 minimal medium with citrate to glucose-containing medium as the sole C source.…”
Section: Discussionmentioning
confidence: 99%
“…It resulted in the identification of all except two of the genes involved in the degradation of the different carbohydrates studied ( Fig. 2; Lessie & Phibbs, 1984;Temple et al, 1998): the fructose utilization gene cluster (PP0792-PP0795), the glucose utilization gene cluster (PP1010-PP1012; Sage et al, 1996), the zwf-pgleda gene cluster (PP1021-PP1024; Petruschka et al, 2002;Hager et al, 2000), the 2-ketogluconate utilization gene cluster (PP3376-PP3380; Swanson et al, 2000) and the gluconate utilization gene cluster (PP3415-PP3417). Only the genes encoding glucose dehydrogenase and gluconate dehydrogenase were not positively identified.…”
Section: Hcamentioning
confidence: 99%
“…The growth substrate(s) within the CF lung is not known, but high concentrations of proteins and amino acids have been found in CF sputum (2,33,48). Since glucose-grown bacteria served as the control comparison in the GeneChip experiments and glucose metabolism is well understood in P. aeruginosa (7,19,22,36,41), we hypothesized that our array data would provide information regarding carbon metabolism in CF sputum. Eleven genes involved in branch chain and aromatic amino acid catabolism were highly up-regulated during growth in CF sputum (Table 1), and genes involved in biosynthesis of these amino acids were repressed.…”
Section: Medium Increased P Aeruginosa Growth Yields (Data Not Shown)mentioning
confidence: 99%